Pengaruh Pemberian Ekstrak Kulit Pisang dan Kulit Nanas terhadap Kadar Kalium Tikus Putih Wistar - Hiqbar Hiqbar; Hadi Kurniawan; Pratiwi Apridamayanti (Journal Syifa Sciences and Clinical Research, 2022)
The waste of banana peels and pineapple peels in its utilization is still very lacking, even though it has the potential to be developed because they have high potassium as potassium intake in the body. The combination of banana peel extract and pineapple peel extract is expected to have a synergistic effect as a potassium supplement. The purpose of this study was to determine serum potassium levels of rats (Rattus norvegicus L.) Wistar with banana peel and pineapple peel extracts. Banana peel and pineapple peel were extracted using the infusion method. The test animals used male and female Wistar rats. The control group was given glucose and sucrose bases, the test group was given doses of 100, 400, and 1000 mg/KgBW of banana peel and pineapple peel extract with glucose and sucrose bases, and the control satellite group and satellite dose of 1000 mg/KgBW. The results of all groups showed normal levels of potassium in blood serum. Potassium levels between each group did not show a significant difference (p≥0.05) in male and female rats. Conclusion: administration of banana peel and pineapple peel extract did not affect the serum potassium level of Wistar rats.